Trends in consumer credit legislation - Curran, Barbara A.; American Bar Foundation (Chicago : University of Chicago Press, 1965)
The book is a collection, analysis, and comparison of statutory materials relating to the different phases of the consumer credit process and to the different types of consumer credit arrangements.
An American Bar Foundation study of statutory regulation of consumer credit.
Includes bibliographical references.
obn 25/01/2019
Loans
Keywords: Loans, Personal; Credit